Analisis Penggunaan Faktor Produksi dan Produktivitas Usaha Budidaya Ikan Bandeng di Desa Petis, Kecamatan Duduk Sampeyan, Kabupaten Gresik - Wachidatus Sa'adah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study analyzes the use of production factors and the productivity of milkfish farming in Petis Village, Duduk Sampeyan District, Gresik Regency. This study used a descriptive quantitative method with partial factor productivity and total factor productivity (TFP) analysis. The results showed that the use of production factors, including 5,200 fry, 100 kg of fertilizer, 50 kg of artificial feed, 5 liters of medicines, 8 liters of supplements, 40 liters of diesel fuel, and 12 workers, resulted in a milkfish production of 720 kg. The productivity of each production factor included 0.138 kg of fry/fish, 7.20 kg of fertilizer/kg, 14.40 kg of artificial feed, 144.00 kg of medicines/liter, 90.00 kg of supplements/liter, 18.00 kg of diesel fuel, and 60.00 kg of labor per person. The TFP value of 5.49 indicates that the milkfish farming business is operating productively and efficiently.